Properties of Frying Shortening Prepared from Lipase-Transesterified Palm Stearin and Palm Kernel Olein Blend - Tee, Siok Bee (2001)
Transesterification process is a vital tool to tailor-make trans-free fats and oils products. Palm stearin (PS) is the solid fraction of palm oil, while palm kernel olein (PKO) is the liquid fraction extract from the palm kernel. The combination of this hard stock and the liquid oil in a transesterificationn process may result in the production of a trans-free plastic frying shortening that can replace the conventional hydrogenated base product. This study was conducted to produce a trans-free frying shortening from PS:PKO blend, via transesterification process using the lipase from Rhizomucor mtehei (Lipozyme IM60, Novo Nordisk, Denmark). The physical and chemical properties of five domestic and imported plastic frying shortenings were analysed so as to obtain information on the functional characteristics of a typical plastic frying shortening. By taking the plastic range of the samples at solid fat content (SFC) of 15-250/0, the imported samples (Samples D and E) fell in the lower temperature range (1l-26°C) compared to domestic sample (Samples A, B and C) (21-40°C) The PS:PKO (w/w) (1:4, 3:7, 2:3, 1:1 and 3:2) blends were transesterified using Lipozyme IM60 lipase at 60°C for 6 h. Results showed that the plastic range of all PS:PKO blends shifted to a lower temperature range as the PKO level increased in the blends. For each of the PS:PKO blends, transesterification also shifted their plastic range to a lower range as compared to their respective control blends. Transesterification utilized the short carbon chains TG (such as LaDD, LaLaD, LaLaM and LaMM) and long carbon chain TG (such as PPP, PPS and POS) to produce TG with the carbon chains that fell within the two ranges. The alteration in TG composition of PS:PKO blends through enzymatic transesterification had lead to the changes in their slip melting point (SMP), SFC, polymorphic fonn, crystallisation and melting behaviour, especially at high temperature range (35-40°C) and therefore explained the improvement in their plastic range. Result of the increase in medium chains TG via transesterification was also exhibited by the change in the melting behaviour. In their melting bahaviour studies, results showed that the higher melting temperature TG was found to reduce corresponding to the increase in the lower melting temperature TG. However, the polymophic forms of the tranesterified samples remained largely unchanged. As the PS level increased in the blends, the concentration of TG with longer chains FA (such as PPP, PPS and POS) also increased, resulting in the increase in SMP and SFC levels, especially at the high temperature ranges (35-40°C). Similar changes were also found in their crystallisation and melting behaviour studies. The polymorpic fonns of the PS:PKO blends also changed as the PS level increased. The higher the PS level, the more β dominating the sample became.